Role of ROS in ischemia-induced lung angiogenesis - Nijmeh, Julie (American Physiological Society, 2010)
Pulmonary artery obstruction and subsequent lung ischemia have been shown to induce systemic angiogenesis despite preservation of normoxia. The underlying mechanisms, however, remain poorly understood. In a mouse model of lung ischemia induced by left pulmonary artery ligation (LPAL), we showed previously, the formation of a new systemic vasculature to the ischemic lung. We hypothesize that LPAL in the mouse increases reactive oxygen species (ROS) production, and these molecules play an initiating role in subsequent lung neovascularization. We used oxidant-sensitive dyes (DHE and H(2)DCF-DA) to quantify ROS and measured the antioxidant-reduced glutathione (GSH) and its oxidized form (GSSG) as indicators of ROS levels after LPAL. The magnitude of systemic neovascularization was determined by measuring systemic blood flow to the left lung with radiolabeled microspheres 14 days after LPAL. An increase in ROS was observed early (30 min: 55% increase in H(2)DCF-DA) after LPAL, with a return to baseline by 24 h. GSH/GSSG was decreased (∼50%) 4 h after LPAL, suggesting earlier ROS upregulation. Mice treated with the antioxidant N-acetylcysteine showed attenuated angiogenesis (62% of wild-type LPAL), and mice lacking Nrf2, a transcription factor important for antioxidant synthesis, resulted in increased neovascularization (207% of wild-type LPAL). Overall, GSH/GSSG was inversely associated with the magnitude of neovascularization. These results demonstrate that LPAL induces an early and transient ROS upregulation, and ROS appear to play a role in promoting ischemia-induced angiogenesis.